A review on wormhole attacks in MANET - Enshaei, Mehdi; Mohd Hanapi, Zurina (Asian Research Publication Network, 2015)
Mobile Ad-hoc Network (MANET) refers to a multi-hop packet based wireless network consist of number of mobile nodes which be able to communicate and move simultaneously, without using any fixed infrastructure. MANET’S are self-organizing networks that can be formed and deformed on the fly. A number of different attacks have been discovered that can be launched against MANETs. Wormhole attackis one such attack that has been recently discovered. Wormhole attack is a very severe and challenging attack because of the fact that it can be launched against any protocol and also due to its ability to be effective in case of encrypted traffic. Enormous amount of work has been done towards the mitigation of wormhole attack and its counter measure. In this paper we have summarize the efforts previously done, our aim here is to provide the researchers a platform where they can find a complete reference to all past work done in regards to the wormhole attack. In the review paper we try to know all the detection techniques and use appropriate one or modify previous related works to have better defense mechanism against wormhole attacks.